Enhanced Biofilm Formation and Membrane Vesicle Release by Escherichia coli Expressing a Commonly Occurring Plasmid Gene, kil - Nakao, Ryoma; Myint, Si Lhyam; Wai, Sun Nyunt; Uhlin, Bernt Eric (Frontiers in Microbiology, 2018)
Escherichia coli is one of the most prevalent microorganisms forming biofilms on indwelling medical devices, as well as a representative model to study the biology and ecology of biofilms. Here we report that a small plasmid gene, kil, enhances biofilm formation of E. coli. The kil gene is widely conserved among naturally occurring colicinogenic plasmids such as ColE1 plasmid, and is also present in some plasmid derivatives used as cloning vectors. Firstly, we found that over-expression of the kil gene product dramatically increased biofilm mass enriched with extracellular DNA in the outer membrane-compromised strain RN102, a deep rough LPS mutant E. coli K-12 derivative. We also found that the kil-enhanced biofilm formation was further promoted by addition of physiologically relevant concentrations of Mg2+, not only in case of RN102, but also with the parental strain BW25113, which retains intact core-oligosaccharide LPS. Biofilm formation by kil-expressing BW25113 strain (BW25113 kil+) was significantly inhibited by protease but not DNase I. In addition, a large amount of proteinous materials were released from BW25113 kil+ cells. These materials contained soluble cytoplasmic and periplasmic proteins, and insoluble membrane vesicles (MVs). The kil-induced MVs were composed of not only outer membrane/periplasmic proteins, but also inner membrane/cytoplasmic proteins, indicating that MVs from both of outer and inner membranes could be released into the extracellular milieu. Subcellular fractionation analysis revealed that the Kil proteins translocated to both outer and inner membranes in whole cells of BW25113 kil+. Furthermore, the BW25113 kil+ showed not only reduced viability in the stationary growth phase, but also increased susceptibility to killing by predator bacteria, Vibrio cholerae expressing the type VI secretion system, in spite of no obvious change in morphology and physiology of the bacterial membrane under regular culture conditions. Taken together, our findings suggest that there is risk of increasing biofilm formation and spreading of numerous MVs releasing various cellular components due to kil gene expression. From another point of view, our findings could also offer an efficient MV production strategies using a conditional kil vector in biotechnological applications.